2008
DOI: 10.1093/alcalc/agn084
|View full text |Cite
|
Sign up to set email alerts
|

Detection Times for Urinary Ethyl Glucuronide and Ethyl Sulfate in Heavy Drinkers during Alcohol Detoxification

Abstract: During alcohol detoxification, EtG and EtS remained detectable in urine for several days. The detection times showed wide inter-individual variations, also after adjusting values for urine dilution and to the estimated times for a completed ethanol elimination.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
150
0
14

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 195 publications
(169 citation statements)
references
References 39 publications
4
150
0
14
Order By: Relevance
“…As far as we know, there are no further studies testing tartrate excretion beyond the day after its consumption. In any case, the values of the combined model of tartrateEtG of consumers≥24h and <72h are in keeping with the kinetics results of studies presented above (Helander et al, 2009;Stalmach et al, 2013;Weinmann et al, 2004;Wurst et al, 2006).…”
Section: Detection Times Of Biomarkers From the Modelsupporting
confidence: 84%
See 1 more Smart Citation
“…As far as we know, there are no further studies testing tartrate excretion beyond the day after its consumption. In any case, the values of the combined model of tartrateEtG of consumers≥24h and <72h are in keeping with the kinetics results of studies presented above (Helander et al, 2009;Stalmach et al, 2013;Weinmann et al, 2004;Wurst et al, 2006).…”
Section: Detection Times Of Biomarkers From the Modelsupporting
confidence: 84%
“…Weinmann et al confirmed by mass spectrometry that after 9 g of ethanol intake (0.16g/kg), EtG reached a maximum concentration at 8-10 h and is detectable over 30 h (Weinmann et al, 2004), this fact is in line with our results. Similarly other studies reported detection up to 48h (~0.5 g/kg) (Wojcik and Hawthorne, 2007)and up to 130h (~5days) in extreme cases of alcohol intoxication (Helander et al, 2009). Tartrate is reported excreted over 24h after acute intake of grape juice (Stalmach et al, 2013).…”
Section: Detection Times Of Biomarkers From the Modelmentioning
confidence: 51%
“…For the analysis of EtG in urine and serum, methods based on GC-MS [14 -16], LC-MS [1, 2, 5, 12, 15 -19] and ELISA [20,21] have been developed. Furthermore, CZE [22,23] and ITP-CZE [24] were applied to the determination of EtG in serum, and a commercial enzyme immunoassay (EIA) for urinary EtG became recently available and was found to be suitable for rapid urine screening [3,25,26]. The literature suggests that the calibration range for EtG in serum has to be in the low mg/L range.…”
Section: Introductionmentioning
confidence: 99%
“…The conjugated minor ethanol metabolites ethyl glucuronide (2 ) and ethyl sulfate (3 ) and fatty acid ethyl esters (4 ) are examples of such tests. Ethyl glucuronide and ethyl sulfate are excreted in urine for a much longer time than ethanol and hence have gained popularity as diagnostically sensitive and specific tests to spot recent alcohol consumption (5)(6)(7). For detection and follow-up of long-term risky or heavy drinking, measurement of the alcohol-related change in the serum transferrin glycoform profile known as carbohydrate-deficient transferrin (CDT) 2 (8, 9 ) has become a standard method, often used in combination with liver function tests (e.g., ␥-glutamyltransferase) (1 ).…”
mentioning
confidence: 99%